The artist's reality : philosophies of art - Rothko, Mark, 1903-1970 (Yale University Press, 2004)
"Mark Rothko (1903-1970) created a new and impassioned form of abstract painting over the course of his career. Rothko also wrote a number of essays and critical reviews during his lifetime, adding his thoughtful, intelligent, and opinionated voice to the debates of the contemporary art world. Although the artist never published a book of his varied and complex views, his heirs indicate that he occasionally spoke of the existence of such a manuscript to friends and colleagues. Stored in a warehouse since the artist's death more than thirty years ago, this manuscript, titled The Artist's Reality, is now being published for the first time"--Publisher's description